1990
DOI: 10.1111/j.1464-410x.1990.tb14893.x
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity Following Cystoscopy: Comparison of Flexible and Rigid Techniques

Abstract: Recent reports on the value of local anaesthetic flexible cystoscopy have emphasised excellent tolerance and preference for the technique over general anaesthetic rigid cystoscopy. However, no study has yet compared the post-operative morbidity rates of these procedures. Tolerance, preference and post-operative symptoms in 100 patients undergoing local anaesthetic flexible cystoscopy were compared with those in 100 patients undergoing general anaesthetic rigid cystoscopy. On initial questioning, 89% of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 5 publications
2
30
0
2
Order By: Relevance
“…[2,5]. Denholm et al compared the tolerability of flexible and rigid cystoscopes and noted that 89% of patients reported flexible cystoscopy as painless [5]. Our results confirm these findings, as we have used small calibred cystoscopes (17F rigid, 16.2F flexible cystoscopes) and demonstrated that instrument type is strongly associated with the pain during cystoscopy.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…[2,5]. Denholm et al compared the tolerability of flexible and rigid cystoscopes and noted that 89% of patients reported flexible cystoscopy as painless [5]. Our results confirm these findings, as we have used small calibred cystoscopes (17F rigid, 16.2F flexible cystoscopes) and demonstrated that instrument type is strongly associated with the pain during cystoscopy.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies have demonstrated similar efficacy between rigid and flexible cystoscopy in identifying tumors [2]. Although excellent tolerability was noted in both techniques, earlier results revealed that male patients prefer flexible cystoscopy in the outpatient clinic rather than rigid cystoscopy in the operating room with general anesthesia [2,4,5]. The major advantages of flexible endoscopy are the ease of performance due to smaller calibre instruments, improved global visualisation of the vesical surface especially in men presumably due to urethral length and the angle required to inspect the bladder, enhanced patient comfort and tolerability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our overall frequency of hematuria after cystoscopy and TURB was 13.7%, compared to reported gross hematuria after flexible cystoscopy in 19% [17]. In all, since symptoms after rigid cystoscopy are reported twice as frequent compared to flexible cystoscopy [20], this puts symptoms in our studies in a positive perspective, having used rigid instruments in all studies.…”
Section: Commentmentioning
confidence: 54%
“…Our study identified an incidence of postflexible-cystoscopy dysuria of 28%, which is at the lower end of the range when compared with reports in the literature (30-54% [1,2,11]). As the incidence found was lower than expected, the sample size of the study was adequate to detect a 50% reduction in dysuria, rather than the 33% reduction specified in the study design.…”
Section: Discussionmentioning
confidence: 56%